Evaluating the parking demand at park and ride facility at Putrajaya public transportation terminal - Syed Adnan, Sharifah Adibah Alyia; Kadar Hamsa, Abdul Azeez (2013)
The purpose of this paper is to analyze the level of parking utilization at two types of parking namely multi-storey and surface parking at Putrajaya public transportation terminal. A parking utilization survey was conducted to determine the parking demand of the users. The analysis of this paper focuses on parking characteristics such as parking accumulation, occupancy, duration, turnover, and volume. The parking demand on weekday was higher than weekend and surface parking shows higher demand than multi-storey parking both on weekend and weekday. The average parking occupancy at surface parking on weekday was 84.5% as compared to level 1 (25%), level 2 (50%) and basement (20%) of the multi-storey parking. The parking duration showed that the users were parked more than 9 hours as they were traveling for work purpose. A high parking demand at the park and ride facility will, eventually, help to achieve the benefits of sustainable transportation.